PREVALENCE OF DIFFERENT POLYP TYPES IN MSI AND MSS AGE AND GENDER MATCHED COHORTS OF COLORECTAL CANCER RESECTIONS. (8th June 2013) - Gibbons, D; Rogers, A; Ng, C H; Geraghty, R; Rhinehart, E; Hyland, J; O'Connell, R P; Winter, D; Mulcahy, H; Doherty, G; O'Donoghue, D; Fennelly, D; et al.
Abstract : Introduction: The sessile serrated pathway has gained increased recognition in recent years. Up to 30% of of colorectal tumours are thought to arise in this manner but its significance remains to be elucidated. Aims/Background: This study sought to establish the prevalence and significance of the sessile serrated pathway in curative resections for colorectal carcinoma. Method: All colorectal carcinomas resected with curative intent, with immunohistochemical characterization of microsatellite status at diagnosis, over an eight year period were identified. 1415 colectomy specimens were identified of which 126 had microsatellite instability (MSI). An age and gender matched MSS cohort was generated. A careful gross examination described and sampled all polyps. All polyps were reviewed, enumerated and classified as SSA (sessile serrated adenoma), adenoma or hyperplastic. Appendiceal polyps were excluded. Mean numbers of polyps, total and subtypes were compared in the MSI and MSS groups. A two tailed t-test was used to test for significance. Results: 57% of MSI cases and 50% of MSS cases had polyps in the resection. In the MSI group there were 5 SSAs, 92 adenomas and 37 hyperplastic polyps (totalling 134). In the MSS group there were 0 SSAs, 62 adenomas and 23 hyperplastic polyps (totalling 95). There were no significant differences in numbers of adenomas, hyperplastic polyps or total polyps in both groups. However there were significantly more SSAs in the MSI group (p=0.0239). Conclusion: Although absolute numbers are low, the finding of an SSA in a cancer colectomy specimen is a strong indicator that the carcinoma will display microsatellite instablity (MSI).